2021
DOI: 10.1172/jci140837
|View full text |Cite
|
Sign up to set email alerts
|

MAL2 drives immune evasion in breast cancer by suppressing tumor antigen presentation

Abstract: Immune evasion is a pivotal event in tumor progression. To eliminate human cancer cells, current immune checkpoint therapy is set to boost the CD8 + T cell-mediated cytotoxicity. However, this action is eventually dependent on the efficient recognition of tumor-specific antigens via T cell receptors. One primary mechanism by which tumor cells evade immune surveillance is to downregulate their antigen presentation. Little progress has been made towards harnessing potential therapeutic targets for enhancing anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 67 publications
3
58
0
Order By: Relevance
“…As predicted, MAL2 knockdown obviously blocked cell proliferation, migration, invasion and EMT progression, and promoted the cell apoptosis of PRAD cells. Consistent with our findings, MAL2 deletion has been shown to block cell growth in breast cancer (BC), and MAL2 has been identified as a possible therapeutic target for BC immunotherapy (13). MAL2 has been found to be upregulated, and silence MAL2 suppressed cell proliferation and invasion in papillary thyroid carcinoma (15).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As predicted, MAL2 knockdown obviously blocked cell proliferation, migration, invasion and EMT progression, and promoted the cell apoptosis of PRAD cells. Consistent with our findings, MAL2 deletion has been shown to block cell growth in breast cancer (BC), and MAL2 has been identified as a possible therapeutic target for BC immunotherapy (13). MAL2 has been found to be upregulated, and silence MAL2 suppressed cell proliferation and invasion in papillary thyroid carcinoma (15).…”
Section: Discussionsupporting
confidence: 86%
“…MAL2 is identified in proteins associated with membrane-binding events, and is an important component of the transcellular mechanism from the lateral wall of the base to the apex (12). Previous studies have shown that MAL2 is involved in the endocytosis of MHC-I complex in breast tumor cells, and reduces cytotoxicity by suppressing tumor antigen presentation (13). However, little is known about the effect of MAL2 in PRAD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported that FOXOs promoted anti-tumor activity by silencing the expression of immunosuppressive proteins, such as inhibiting the expression of Programmed cell death 1 ligand 1 (PD-L1) to cause the immune escape phenomenon of tumor cells (23). Finally, among the genes co-expressed with CMTMs, studies have reported that MAL2, which was positively correlated with the expression of CMTMs, can act as an oncogene to inhibit tumor antigens and promote tumor immune escape (24). This indicated that the CMTM family may also change the immune microenvironment and regulate the malignant process of ovarian cancer by co-expressed genes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, treatment with a BRAF inhibitor rapidly restored MHC-I expression and improved T-cell recognition [117]. Similarly, transmembrane protein Myelin and lymphocyte 2 (MAL2) that is frequently overexpressed in breast cancer [118] associates with pMHC-I complexes to promote endocytosis and degradation [119]; MAL2 knockdown improved tumor recognition and T-cell activation [119].…”
Section: Mhc-i Expression In Cancer: Implications For Immunotherapymentioning
confidence: 99%